2021
DOI: 10.1016/s2352-4642(20)30342-4
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcomes of neonatal SARS-CoV-2 infection in the UK: a prospective national cohort study using active surveillance

Abstract: Background Babies differ from older children with regard to their exposure to severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However, data describing the effect of SARS-CoV-2 in this group are scarce, and guidance is variable. We aimed to describe the incidence, characteristics, transmission, and outcomes of SARS-CoV-2 infection in neonates who received inpatient hospital care in the UK. Methods We carried out a prospective UK population-based cohort stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

25
290
4
28

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 234 publications
(347 citation statements)
references
References 27 publications
25
290
4
28
Order By: Relevance
“…Our rate of SARS-CoV-2+ infants in the first 3 days of life, 7.4%, is higher than the AAP reported rate of 1.7%, 23 the United Kingdom Obstetric Surveillance System, 5%, 34 in the Spanish data, 5.2%, 27 and that seen in the worldwide review of infants of over 660 pregnant women with COVID-19, 4%, 35 but it is consistent with that seen in the Italian data, 6.1%, 33 and in another New York hospital (Elmhurst), 6.7%. 24 Although it may appear that our neonatal hospitalization rate is high compared with that reported in the literature (5.6 per 10,000 livebirths in the United Kingdom), 36 we do not have a true numerator, so that even if all 4 hospitalized neonates in our study were American (instead of from 31 countries), our hospitalization rate would be 0.01 per 10,000.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Our rate of SARS-CoV-2+ infants in the first 3 days of life, 7.4%, is higher than the AAP reported rate of 1.7%, 23 the United Kingdom Obstetric Surveillance System, 5%, 34 in the Spanish data, 5.2%, 27 and that seen in the worldwide review of infants of over 660 pregnant women with COVID-19, 4%, 35 but it is consistent with that seen in the Italian data, 6.1%, 33 and in another New York hospital (Elmhurst), 6.7%. 24 Although it may appear that our neonatal hospitalization rate is high compared with that reported in the literature (5.6 per 10,000 livebirths in the United Kingdom), 36 we do not have a true numerator, so that even if all 4 hospitalized neonates in our study were American (instead of from 31 countries), our hospitalization rate would be 0.01 per 10,000.…”
Section: Discussionmentioning
confidence: 57%
“…Our study is limited by neonatal sample size that did not allow for detection of noninferiority in neonatal outcomes by exposures of interest. The exceptionally low reported hospitalization rate in the literature 36 indicates it may be nearly impossible to demonstrate a clinical benefit from disrupting Baby-Friendly practices. We were also limited by our lack of ability to verify responses with IP addresses, which would have allowed us to verify the global location of a respondent and better confirm genuine responses and eliminate duplicate responses.…”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the Article by Chris Gale and colleagues reporting data from active surveillance of neonatal severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection during the first COVID-19 wave in the UK. 1 The authors are to be commended for the detailed presentation of their data, and the overall carefully worded interpretation.…”
mentioning
confidence: 99%
“…A synthesis and systematic review of 176 published cases reported recently that 70 and 30% of infections were due to environmental and vertical transmission, respectively, and suggested that a lack of mother-neonate separation from birth was associated with late SARS-CoV-2 infection, while breastfeeding was not ( 47 ). However, a population-based prospective national cohort study in the UK supported guidance to avoid the routine separation of mother and baby because neonatal SARS-CoV-2 infection was uncommon and most babies were only mildly affected ( 48 ). Moreover, it should be noticed that an excretion of SARS-CoV-2 has been found in COVID-19-infected mothers' breast milk ( 49 ), yet breastfeeding does not seem to significantly increase the risk of maternal-fetal transmission.…”
Section: Transmission Of Covid-19: Mother To Neonatesmentioning
confidence: 99%